Hubungan Beban Kerja Dengan Kinerja Perawat Dalam Pendokumentasian Asuhan Keperawatan Pada Pasien Di Ruang Rawat Inap - Ismafiaty Ismafiaty; Lilis Rohayani; Jeany Nur Aini (Jurnal Keperawatan Komplementer Holistic e-ISSN 2988-3709 (online), 2023)
This study aims to determine the relationship between workload and nurse performance in documenting nursing care for patients in the Pavilion Inpatient Room of Dustira Cimahi Hospital. Method: This research is a correlation descriptive study using cross sectional. The population and sample in this study were all nurses working in the Pavilion Inpatient Room at Dustira Cimahi Hospital, totaling 40 people. Data analysis was performed univariately and bivariately using the Chi-Square test. Research results: 55% of nurses have a light workload, 57.5% of nurses carry out complete Askep documentation performance and there is a significant relationship between workload and nurse performance in Askep documentation in the Pavilion Inpatient Room of Dustira Cimahi Hospital, with p- value = 0.000. Suggestion: Hospitals are expected to be able to provide nursing care documentation training to nurses in a comprehensive and continuous manner.